Criminology For Dummies - Briggs, Steven; Briggs, Steven (For Dummies, 2021)
Explore the world of crime and punishment Police, forensics, and detective stories dominate our TV screens and bookshelves?from fictional portrayals such as Silence of the Lambs and Law and Order to lurid accounts of real-life super-criminals like Pablo Escobar and Al Capone. As well as being horribly fascinating, knowledge of what makes criminals tick is crucial to governments, who spend billions of dollars each year trying to keep their people safe. Criminology brings disciplines like psychology, biology, and economics together to help police and society solve crimes?and to prevent them before they even happen. The new edition of Criminology For Dummies shines a light into the dark recesses of the criminal mind and goes behind-the-scenes with society's response to crime, putting you right on the mean streets with cops and criminals alike. Along the way, you'll learn everything a rookie needs to survive, including basic definitions of what a crime is and how it's measured; common criminal motivations, thinking, and traits; elementary crime-solving techniques; the effects on and rights of victims; and more. Understand types of crime, from white-collar to organized to terror attacks Follow law-enforcement officials and agencies as they hunt the bad guys Meet key players in criminal justice and see how and why the guilty are punished Check out jobs in the field Whether you plan to enter the criminal justice field or just want to know more about what turns some people to the dark side?and how the thin blue line fights back?this is your perfect guide to criminology basics.